Rydberg-State Excitation and Ionization of Argon Atoms Subject to Strong Circularly Polarized Two-Color Few-Cycle Laser Fields - Wang, Zhiqiang; Quan, Wei; Wang, Yanlan; Hao, Xiaolei; Chen, Jing; Liu, Xiaojun (Chinese physics letters, 2025)
The ultrafast excitation dynamics of atoms and molecules exposed to circularly polarized two-color (CPTC) laser fields constitute a fascinating topic in attosecond science. Although extensive research has established the relationship between the Rydberg state excitation (RSE) yields and the CPTC field parameters, such as field amplitude ratios and helicity of two components, the role of the relative phase ( ϕ ) in modulating RSE efficiency remains unclear. In this work, we theoretically investigate the ϕ dependence of RSE and ionization yields in the co-rotating and counter-rotating circularly polarized two-color (CPTC) few-cycle laser fields by a semiclassical model. We find that, in co-rotating CPTC fields, both RSE and ionization yields display pronounced oscillations as a function of ϕ and these oscillations are significantly suppressed in the counter-rotating configuration, particularly for ionization yields. Moreover, the ratio of RSE to ionization yields exhibits an out-of-phase oscillatory pattern between low- and high-intensity regimes. These results can be comprehended by the unique feature of ϕ dependence of CPTC few-cycle fields, based on our semiclassical analysis. Our results demonstrate that phase-controlled CPTC fields offer a versatile tool for steering ultrafast ionization and RSE dynamics of atoms and molecules.